2019
DOI: 10.1161/circep.119.007661
|View full text |Cite
|
Sign up to set email alerts
|

Novel Irrigated Temperature-Controlled Lattice Ablation Catheter for Ventricular Ablation

Abstract: Background: Ventricular tachycardia ablation is often limited by insufficient lesion creation. A novel radiofrequency catheter with an expandable lattice electrode has a larger surface area capable of delivering higher currents at a lower density to potentially increase lesion dimensions without overheating. Methods: This 8F bidirectional irrigated catheter (Sphere-9, Affera Inc) has a 9 mm spherical lattice tip (“lattice”) with an effective surface are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…The system also provides an indication of proximity between the catheter and the tissue by continuously evaluating impedance between each of the mini-electrodes and the center electrode, highlighting electrodes with elevated local impedance. 9,10 The center of the lattice contains a protected irrigation nozzle with micropores that provide homogeneous cooling unaffected by pressure applied to the catheter or the angle of tissue engagement.…”
Section: Ablation Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The system also provides an indication of proximity between the catheter and the tissue by continuously evaluating impedance between each of the mini-electrodes and the center electrode, highlighting electrodes with elevated local impedance. 9,10 The center of the lattice contains a protected irrigation nozzle with micropores that provide homogeneous cooling unaffected by pressure applied to the catheter or the angle of tissue engagement.…”
Section: Ablation Systemmentioning
confidence: 99%
“…In preclinical studies, it produced rapid and durable atrial lesions, and ventricular lesions with a maximal depth that was twice of standard irrigated catheters. 9,10 In humans, this technology produced rapid and durable PVI with a similar safety profile to other RF technologies. 11,12 However, given the potential safety benefits of PFA, we sought to develop a system that can deliver either focal RFA or PFA using the same catheter.…”
Section: Introductionmentioning
confidence: 99%
“…However, they changed the baseline R by adjusting the series R in the circuit instead of changing the R of normal saline in the container. Shapira-Daniels et al changed the contact area between the negative plate and the skin (the parallel circuit reduces the impedance), so as to achieve the purpose of reducing the impedance ( 15 ). As a result, they found the opposite pattern that this study found: RFCA at a lower R resulted in increased tissue heating and led to larger lesion dimensions because of the increased current delivery ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…To develop a robust ex vivo model with physiological and clinical relevance, an RCA was conducted to isolate potential parameters influencing cardiac ablation outcomes based on prior model development and physiology literature. 5,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Model parameters were subdivided into three categories: ex vivo tissue parameters, media parameters, and impedance parameters. Each parameter was identified alongside its mechanism of influencing ablation outcomes (Central Illustration).…”
Section: Identification Of Parameters Influencing Myocardial Tissue A...mentioning
confidence: 99%